GOPAY AS A PRACTICAL PAYMENT TOOL FOR MILLENNIAL GENERATIONS IN THE DIGITAL ERA - Robetmi Jumpakita Pinem (Politeknik Negeri Batam, 2020)
Activities that require very high speeds make people think of shortcuts in doing their work so that they are faster and more practical. One of the activities that humans do very often is buying and selling transactions. Every human being makes transactions almost every day whether to buy food, daily necessities or even now an electronic payment system is emerging that can be used to process payments both for paying certain transportation and also for purchasing certain products, especially food. The presence of Gopay electronic payment systems in Indonesia is one of the innovations that is currently increasingly mushrooming in Indonesia. Data collection was carried out through questionnaires and elaborated with additional information from interviews and observations. Data is processed using SPSS Version 21.0. The frequency of using Gopay in young people aged between 18-20 years on average sometimes to frequently use Gopay as a means of payment because of practical reasons, often get discounts and prefer cashless. Gopay is used for Go-ride / Go-car and Gofood payments and other payments such as Go-send payments, credit purchases, Go-me and other purchases. Dominant respondents do not agree if Gopay replaces money as a whole but agree if Gopay replaces credit cards because the origin is cheaper and there is no interest and monthly fees. Gopay refilling process can be done easily because it can be done in many ways, namely refilling through the Gojek driver, through convenient stores, through atm machines and other ways. The difficulty when refilling Gopay is very often the driver of the motorcycle does not have a balance and it often happens.